The Effects of Learning Models of Discovery Learning and Learning Interest on Social Science Learning Outcomes in Grade VII of Junior High School of Al-Azhar Medan - Andi Irawan; Dede Ruslan; Aman Simare mare (BIRCU, 2019)
This study deals with the effects of learning models of discovery learning and learning interest on social science learning outcomes in grade VII of Junior High School of Al-Azhar Medan. This study was conducted in the Even Semester of the Learning Year 2018/2019, which began in April to May 2019 with stages: observation, determining the experimental class and the control class, preparation of research instruments, instrument testing, pre-test administration, giving questionnaires of interest, treatment, giving post-tests, processing data, analyzing data, drawing conclusions. The conclusion of this study were there is a significant effects of learning models of discovery learning on social science learning outcomes in grade VII of Junior High School of Al-Azhar Medan (Fcount = 306,594; P = 0,000). There is a significant effects of learning interest in social science learning outcomes in grade VII of Junior High School of Al-Azhar Medan (Fcount 69,071; P = 0,000). There is a significant interaction between Discovery Learning models and learning interest in social science learning outcomes in grade VII of Junior High School of Al-Azhar Medan (Fcount = 5,288; P = 0,012).